2014
DOI: 10.1051/0004-6361/201424325
|View full text |Cite
|
Sign up to set email alerts
|

A new correction of stellar oscillation frequencies for near-surface effects

Abstract: Context. Space-based observations of solar-like oscillations present an opportunity to constrain stellar models using individual mode frequencies. However, current stellar models are inaccurate near the surface, which introduces a systematic difference that must be corrected. Aims. We introduce and evaluate two parametrizations of the surface corrections based on formulae given by Gough (1990, LNP, 367, 283). The first we call a cubic term proportional to ν 3 /I and the second has an additional inverse term p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
339
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 221 publications
(343 citation statements)
references
References 47 publications
(84 reference statements)
4
339
0
Order By: Relevance
“…GN93: Grevesse & Noels (1993); GS98: Grevesse & Sauval (1998). KBC08: Kjeldsen et al (2008); BG14: Ball & Gizon (2014).…”
Section: Stellar Model Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…GN93: Grevesse & Noels (1993); GS98: Grevesse & Sauval (1998). KBC08: Kjeldsen et al (2008); BG14: Ball & Gizon (2014).…”
Section: Stellar Model Comparisonsmentioning
confidence: 99%
“…These 11 initial guesses were then optimised using a downhill simplex optimisation (Nelder & Mead 1965), with all models with a χ 2 < 1000 being recorded. In this latter case, we optimised the merit function without Δν and ν max , instead using the individual oscillation frequencies, corrected according to the cubic correction given by Ball & Gizon (2014).…”
Section: Free Model Mode Frequencies and Analytical Surface Correctimentioning
confidence: 99%
“…Oscillation mode frequencies were computed by internal calls to adipls. Model frequencies were corrected for surface effects using the two-term (or combined) correction described by Ball & Gizon (2014). For a given choice of mass M, initial metal abundance Z i , initial helium abundance Y i and mixing-length parameter α, mesa evolved a stellar model from a pre-main-sequence model with central temperature T c = 9 × 10 6 K and found the bestfitting age and surface correction parameters for those input parameters.…”
Section: Modellingmentioning
confidence: 99%
“…The P N values are averages over several sets of oscillation modes. The gyrochronology ages are calculated from Barnes and Kim (2010), Mamajek and Hillenbrand (2008), and 4.5 Gyrochronology with the same input physics as in Ball and Gizon (2014). Initial fits were determined using the SEEK method (Quirion et al 2010) to compare a grid of models to observed spectroscopic and global asteroseismic parameters.…”
Section: Comparing Asteroseismic and Surface Variability Periodsmentioning
confidence: 99%
“…The 11 initial guesses were optimized in five parameters (age, mass, metallicity, helium abundance, and mixing length) using a downhill simplex (Nelder and Mead 1965) to match spectroscopic data ) and individual oscillation frequencies, computed with ADIPLS (Christensen-Dalsgaard 2008) and corrected according to the cubic correction by Ball and Gizon (2014). As in Ball and Gizon (2014), the seismic and nonseismic observations are weighted only by their respective measurement uncertainties. Best-fit parameters and uncertainties are estimated from ellipses bounding surfaces of constant χ 2 for all the models determined during the optimizations, corresponding to a total of about 3000 models for each star.…”
Section: Comparing Asteroseismic and Surface Variability Periodsmentioning
confidence: 99%